Peningkatan Soft Skills Melalui Pelatihan “Communication for job Seekers” Bagi Kelompok Belajar Siswa di PT Lintas Digital Makmur - Sahara, Sahara; Ilmi, Miftahul; Hariselmi, Hariselmi; Simamora, Helprida (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This service activity aims to improve Soft skills through Communication for job seekers training at PT Lintas Digital Makmur. The trainees are study group students currently in the third grade of vocational school. Those who are about to graduate and enter the world of work. The method of Service is divided into four stages: observing, planning, implementing, and evaluating. Based on the stages of activities that have been planned, community service activities are produced such as: (1) observing in the field to obtain information and analyze what needs are needed by students in their learning groups (2) Planning is the stage where preparing everything to support service activities, (3) implementing activities that have been planned, namely by providing direct training to students with lecture, (4) evaluating is an activity to distribute questionnaires containing questions in the form of google form. The conclusion from the results of this dedication is that this training is very helpful for students in preparing to enter the workforce. Presentations, discussions, and simulations make students confident and eager to be active in each session. As a result, students can understand and answer interview questions effectively. Therefore, similar training for other groups of job seekers is highly recommended in the future.